2013
DOI: 10.1016/j.compfluid.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A conservative strategy to couple 1D and 2D models for shallow water flow simulation

Abstract: A 1D-2D coupled numerical model is presented in this work. 1D and 2D models are formulated using a conservative upwind cell-centered finite volume scheme. The discretization is based on cross sections for the 1D model rios. It is also applied to a real world configuration, where the flood wave propagation in the river bed is simulated by means of a 1D model and the inundation of the riverside is dealt with a 2D model. The computational gain is also analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 24 publications
0
38
1
4
Order By: Relevance
“…On the other hand, water depths measured at Gauge 4 are different from the ones at Point 5 (in Figure 9a), where Point 4 is closest to the inlet of the floodplain and further away from the wall than Point 5. Observe the opposite in the results provided by Morales et al [10] and shown in Figure 10, where water depths at Points 4 and 5 are often undistinguishable at the adopted graphic scale, while smaller water depths are computed at Gauge 10 (see Figure 10a,b). For each simulation, the discharges leaving the domain and computed by the FLO model are very similar, and only the peak region is shown in Figure 11.…”
Section: Test 1: Comparison With the Results Of Morales Et Al [10]contrasting
confidence: 39%
See 4 more Smart Citations
“…On the other hand, water depths measured at Gauge 4 are different from the ones at Point 5 (in Figure 9a), where Point 4 is closest to the inlet of the floodplain and further away from the wall than Point 5. Observe the opposite in the results provided by Morales et al [10] and shown in Figure 10, where water depths at Points 4 and 5 are often undistinguishable at the adopted graphic scale, while smaller water depths are computed at Gauge 10 (see Figure 10a,b). For each simulation, the discharges leaving the domain and computed by the FLO model are very similar, and only the peak region is shown in Figure 11.…”
Section: Test 1: Comparison With the Results Of Morales Et Al [10]contrasting
confidence: 39%
“…Due to the different resistance law in the 1D channel and in the floodplain, water depths computed over the coupled 1D-2D mesh are slightly higher than the ones over the 2D mesh, with the highest difference less than 0.01 m. On the opposite side, the results provided by Morales et al by their coupled procedure show large differences with respect to the ones computed by their 2D model. Morales et al [10] justify these differences with the choice of the Manning coefficient in the 1D channel and its adjustment due to coupling strategies. See the results of the two models, for both mixed and 2D meshes, shown in Table 1.…”
Section: Test 1: Comparison With the Results Of Morales Et Al [10]mentioning
confidence: 99%
See 3 more Smart Citations